PRAKTEK BERBAGI DALAM KOMUNITAS VIRTUAL DI FACEBOOK: Studi Netnografi pada Komunitas Fotografi Indonesia - Haris Pakaya; Stepanus Bo'do; Andi Akifah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
This study aims to describe various cultural practices in the KFI virtual community and interpret the meaning of The Power Of Sharing which is the community's slogan on social media facebook. This study uses a qualitative method with a netnographic approach. Research data obtained from elicit data, archive data, and field notes. Netnography research stages are quite flexible and less time consuming because the research location is in a virtual space and all data is available digitally. The immersive netnography strategy allows researchers to enter into community interactions, by participating in experiencing routines and rituals in the original social setting of the virtual community being studied. The results of the study show that first, sharing is defined specifically by the KFI community, namely sharing knowledge in the context of the art of photography. Second, the practice of sharing culture is developed and practiced together by members of the KFI community through virtual communication mediated by Facebook as a digital network. The spirit and practice of sharing is the original culture of the Internet virtual community, which is the spirit and strength of KFI. Third, the culture of sharing becomes the glue for members of this community in the virtual world. This culture has become the identity of the KFI community that distinguishes it from other communities as well as allows it to establish relationships with other virtual communities.